La Revista de la Escuela Superior de Guerra "Tte Grl Luis María Campos" ; no. 584/2013 - Escuela Superior de Guerra Tte Grl Luis María Campos (Argentina) (2013)
Ejemplar: Revista de la ESG. Año 91, no. 584 (mayo-ago. 2013). -- 160 p.